Characteristics of smoke movement with forced ventilation by movable fan in a tunnel fire. (April 2017) - Zhou, Tiannian; Liu, Jiahao; Chen, Qinpei; Chen, Xiao; Wang, Jian
Abstract: A sequence of experiments involving a fan with varying inclined angles and distances from a fire source were conducted in a full-scale tunnel to investigate the characteristics of smoke movement with forced ventilation by a movable fan. The phenomenon of smoke movement was described by a laser visualization technique, and the backlayering in the presence of ventilation is discussed in this paper. The results of the experiment demonstrate that the distance between the movable fan and the fire source has a critical range, where the effects of smoke exhaust on reducing the maximum temperature under the ceiling and preventing the backlayering are more significant when the fan was placed in this distance range. However, the disadvantage of faster smoke moving downstream is that it might be adverse to a safe evacuation during tunnel fires. In addition, it was determined that the performance of smoke exhaust in a horizontal path was better than that of an inclined angle within a limited distance, but there was no obvious difference when the distances were large.